Granulocyte macrophage colony stimulating factor (GM-CSF), the critical intermediate of inflammation-induced fetal membrane weakening, primarily exerts its weakening effect on the choriodecidua rather than the amnion. (1st January 2020) - Sharma, Anudeepa; Kumar, Deepak; Moore, Robert M.; Deshmukh, Aditi; Mercer, Brian M.; Mansour, Joseph M.; Moore, John J.
Abstract: Introduction: We have previously demonstrated two associations of PPROM, (1) inflammation/infection (modeled by tumor necrosis factor (TNF)) and (2) decidual bleeding (modeled by thrombin), both decrease fetal membrane (FM) rupture strength in-vitro . Furthermore, Granulocyte-Macrophage-Colony-Stimulating-Factor (GM-CSF) induced by both TNF and thrombin is a critical intermediate, necessary and sufficient for weakening by either agent. The amnion is the strength component of FM and must weaken for FM to rupture. It is unclear whether GM-CSF weakens amnion (AM) directly, or initially targets choriodecidua (CD) which secondarily releases agents to act on amnion. Methods: Full thickness FM fragments were treated with/without GM-CSF. Some were preincubated with alpha-lipoic acid (LA), a known inhibitor of FM weakening. The FM fragments were then strength-tested. Separately, FM fragments were initially separated to AM and CD. AM fragments were cultured with Medium ± GM-CSF and then strength-tested. In other experiments, CD fragments were cultured with Medium, GM-CSF, LA, or LA + GM-CSF. Conditioned medium from each group was then incubated with AM. AM was then strength-tested. Matrix Metalloproteinases (MMPs) and Tissue Inhibitors of Matrix Metalloproteinases (TIMPs) were analyzed by Mutiplex Elisa. Results: GM-CSF weakened intact FM which was blocked by LA. GM-CSF did not weaken isolated AM. However, GM-CSF conditioned CD media weakened AM and this weakening was inhibited by LA. GM-CSF treatment of CD increased MMPs 2, 9, and 10, and decreased TIMPs 1–3. LA reversed these effects. Conclusions: GM-CSF does not weaken amnion directly; GM-CSF acts on CD to increase proteases and decrease anti-proteases which secondarily weaken the amnion. Highlights: GM-CSF is necessary and sufficient for inflammation induced membrane weakening. GM-CSF directly causes fetal membrane weakening which is blocked by α-lipoic acid. GM-CSF does not act directly on amnion to weaken fetal membranes. GM-CSF targets choriodecidua which secondarily causes amnion weakening. GM-CSF produces specific MMPs and decreases specific TIMPs with weakening.